2020
DOI: 10.3390/ijms22010088
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Biomarkers for Nephrotic Syndrome

Abstract: Nephrotic syndrome represents the clinical situation characterized by presence of massive proteinuria and low serum protein caused by a variety of diseases, including minimal change nephrotic syndrome (MCNS), focal segmental glomerulosclerosis (FSGS) and membranous glomerulonephropathy. Differentiating between diagnoses requires invasive renal biopsies in general. Even with the biopsy, we encounter difficulties to differentiate MCNS and FSGS in some cases. There is no other better option currently available fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…In a urinary sample, sediment cells, proteins, miRNAs, and mRNAs can be used as biomarkers to diagnose kidney injury (22)(23)(24). The number of cells in urinary sediment samples is small, and the level of total RNA is too low to be used for RNAseq assay.…”
Section: Discussionmentioning
confidence: 99%
“…In a urinary sample, sediment cells, proteins, miRNAs, and mRNAs can be used as biomarkers to diagnose kidney injury (22)(23)(24). The number of cells in urinary sediment samples is small, and the level of total RNA is too low to be used for RNAseq assay.…”
Section: Discussionmentioning
confidence: 99%
“…Urine is an ideal source of biomarkers and provide valuable insight on renal pathophysiology. Podocyte cytoskeleton is regulated by several miRNAs, including miR-30, miR-132, miR-134 and miR-29a (Tsuji et al, 2020) [27]. In the present study, the observed upregulation of all the four miRNAs (miR-1, mir-215, miR-335, let-7a) in both SSNS and SRNS versus healthy controls implies of podocyte injury, aberrant expression of these microRNAs and their consequent role in the pathogenesis of NS.…”
Section: Discussionmentioning
confidence: 99%
“…(Patnaik et al, 2018). The miRNA‐30a remains a plausible molecular marker to predict drug resistance and pathological type of NS (Sui et al, 2014). Intrarenal expression of miR‐19b was overexpressed (2.5–3 fold) in MesPGN renal tissues.…”
Section: Mirnas In Fsgsmentioning
confidence: 99%
“…miRNAs in peripheral blood might be treated as the molecular biomarkers of human disease. Sui et al (2014) studied the expression levels of three microRNAs (miR‐181a, miR‐483‐5p, and miR‐557) in the serum of NS patients and found miR‐181a alone was significantly upregulated in patients with NS as compared with healthy controls. Zhang et al (2015) profiled miRNAs in plasma samples from a cohort of patients with FSGS and found that miR‐186 expression was correlated with proteinuria level and might be served as biomarkers for FSGS (Zhang et al, 2015).…”
Section: Circulating and Urinary Mirnasmentioning
confidence: 99%